A pinch of poison [large type] - Maxwell, Alyssa (Maxwell, Alyssa. Lady and lady's maid mysteries., 2018)
"In post-World War I England, Lady Phoebe Renshaw and her lady's maid, Eva Huntford, encounter an uncharitable killer at a charity luncheon sponsored by a posh school for girls. To find the killer, Lady Phoebe steps in to handle the wealthy young debutantes with tact and discretion, while Eva cozies up to the staff"--